2017
DOI: 10.1080/02702711.2017.1306602
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Engaged Teachers on Implementation Fidelity and Reading Skill Gains in a Blended Learning Reading Program

Abstract: The number of K-12 classrooms adopting blended learning models is rapidly increasing and represents a cultural shift in teaching and learning; however, fidelity of implementation of these new blended learning programs varies widely. This study aimed to examine the role of teacher engagement in student motivation and achievement in a blended learning environment. Reading skill data were analyzed from 19,366 students across 624 schools led by teachers defined as engaged users of a blended learning reading progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
2
10
0
7
Order By: Relevance
“…The availability of digital technology in and around the classroom and the development of pedagogy through technology integration led to the introduction of b-learning approaches in the educational proocess (Hong & Samimy, 2010;Schechter, Kazakoff, Bundschuh, Prescott & Macaruso, 2017). According to Sharma (2010), b-learning has been in practice for more than 20 years in developed countries, and contrarily to what people may think in the South African context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The availability of digital technology in and around the classroom and the development of pedagogy through technology integration led to the introduction of b-learning approaches in the educational proocess (Hong & Samimy, 2010;Schechter, Kazakoff, Bundschuh, Prescott & Macaruso, 2017). According to Sharma (2010), b-learning has been in practice for more than 20 years in developed countries, and contrarily to what people may think in the South African context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Rolfe and Gray (2011) suggested the evaluation of the effectiveness of self-directed studies that are aided with distance learning resources appropriate for modern educational models. The literature also shows that, the implementation of BL is more successful with instructor motivation in the classroom, but unfortunately, there is a lack of adequate research on instructor motivation with regard to integrating educational technology in the classroom (Schechter, Kazakoff, Bundschuh, Prescott, & Macaruso, 2017). While online instructional technologies are becoming more popular in HEIs, the instructor's opinions and beliefs regarding online learning tend to be generally negative (Patchan, Schunn, Sieg, & McLaughlin, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The blended learning approach utilized in this study, Lexia Reading Core5 Ò (Core5; Lexia Learning 2014) was chosen based on prior studies of demonstrated efficacy (Schechter et al 2017;Schechter et al 2015;O'Callaghan et al 2016) as well as features that address key areas of effective instruction, including clear objectives, frequent assessments of student progress, personalized learning, and ample opportunities for exposure to academic printed materials (Espinoza 2008;Francis et al 2006;Goldenberg 2012). The program is designed to accelerate reading skills in students who are behind their peers as well as sustain and increase progress for on-level and above-level readers.…”
Section: Blended Learning Approach Used In Study Schoolsmentioning
confidence: 99%